2013
DOI: 10.1071/fp12251
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of root proteome to drought stress in drought sensitive and tolerant sunflower inbred lines

Abstract: Productivity of sunflower (Helianthus annuus L.), the fourth most important oilseed crop, is strongly dependent on water availability. To search for genetic variation in the ability of roots to grow into drying soil, 16 sunflower lines were screened in 2 years field experiments by imposing drought stress at flowering stage. The results differentiated RGK 21 and BGK 329 as the most sensitive and tolerant lines respectively. The time course physiological assay of these lines at seedling stage revealed roots as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…The level of ROS scavengers, such as ascorbate peroxidase 2-like protein and Cu/Zn superoxide dismutase in roots, increased in drought-tolerant sunflower ( Helianthus annuus L .) inbred line, but decreased in the sensitive variant [ 52 ]. A pathogenesis-related protein (PRP10) (spot R55) was significantly induced in the roots of wild wheat plants under drought stress in the present study ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of ROS scavengers, such as ascorbate peroxidase 2-like protein and Cu/Zn superoxide dismutase in roots, increased in drought-tolerant sunflower ( Helianthus annuus L .) inbred line, but decreased in the sensitive variant [ 52 ]. A pathogenesis-related protein (PRP10) (spot R55) was significantly induced in the roots of wild wheat plants under drought stress in the present study ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…The responses of root or leaf proteome to abiotic stress, such as drought stress [ 52 , 67 ], salt stress [ 14 ], nitrate availability [ 68 ], and cadmium stress [ 69 ], have been reported in various plant species, including rice, soybean, sunflower, and maize. The contradictory results were concluded about the alteration of carbohydrate metabolism in various plant species under drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…The productivity of sunfl ower, one of the most important oilseed crops, is severely affected by drought stress. Proteomics data indicated that changes in energy usage, water transport and ROS scavenging are important mechanisms for maintaining root growth as the soil dries (Ghaffari et al 2013 ). Proteome analysis of Jatropha curcas , an important biodiesel crop, was performed on the seed oil bodies, and important differences are outlined in its oleosins (Popluechai et al 2011 ).…”
Section: Oilseed Crop Proteomicsmentioning
confidence: 98%
“…The number of proteins clustered into these functional groups increased consistently for the six proteomes ( Then, we conducted the functional classification for the DAPs where each function group should contain a minimum of three proteins in one of the six proteomes. The DAPs were clustered into the following 26 functional groups: Abiotic/biotic stress (1), Functional enzyme (2), Development (3), Secondary metabolism (4), Protein degradation (5), Unclassified (6), Amino acid metabolism (7), Phyto-hormone metabolism (8), Signaling regulation (9), Cell organization (10), Nucleotide metabolism (11), Cell wall synthesis/modification (12), DNA synthesis (13), Lipids metabolism (14), Major CHO metabolism (15), Minor CHO metabolism (16), Protein targeting and vesicle transport (17), Redox balance (18), Regulation of transcription (19), RNA processing (20), TCA cycle (21), Transport (22), Glycolysis (23), Mitochondrial electron transport/ATP synthesis (24), Protein modification (25), and Protein synthesis (26). Proteins included in functional classification are provided in Table S5.…”
Section: The Drought-induced Proteins and Functional Classificationsmentioning
confidence: 99%
“…Proteomics has been widely used in the investigation of structural and functional interactions of proteins at a given time point at the whole proteome level. These drought-induced proteins are related to water transport, reactive oxygen species (ROS) scavenging, carbohydrate metabolism, and cell wall modification, which ultimately contribute to growth maintenance of roots under stressful conditions [25][26][27][28]. The root tip has three main zones: a zone of cell division (cells are actively dividing), a zone of elongation (cells increase in length), and a zone of maturation.…”
Section: Introductionmentioning
confidence: 99%